Developing of sustainability balanced scorecard for the chemical industry: preliminary evidence from a case analysis - Fülöp, G.; Hernádi, B.; Jalali, M.; Meidute-Kavaliauskiene, I.; Ferreira, F. (Engineering Economics, 2014)
Companies today operate in an increasingly turbulent environment, with multiple (and sometimes competing) demands. Among these there is sustainability. No longer merely a buzzword, sustainability is becoming a mainstay of organizational operations, and a strategic pre-requisite for long term competitive advantages and business excellence. Crafting and implementing of strategy adapted to the company’s external context and internal resources and capabilities are fundamental, and sustainability needs to be a central element to any such strategy. As such, tools are required that can bring these components together. Long used for performance management and strategic management more generally, the Balanced Scorecard (BSC) could plausibly constitute such a framework, if appropriately extended to include sustainability concerns. The aim of this paper is thus to develop such an extension, through creation of a Sustainability Balanced Scorecard (SBSC), which includes social and environmental perspectives and their interactions with the traditional perspectives. We outline the structure for a SBSC, which takes companies’ overall sustainability objectives into account, as well as the steps required for its development. A case study of the formation and introduction of a “credible” sustainability strategy in the chemical industry is presented. The results demonstrate the usefulness of the SBSC in pursuing sustainability strategies, and provide preliminary evidence that introduction of such a system is likely to lead to fundamental changes in the way a company is managed. Practical implications and managerial guidelines are also reported.